EVALUATION OF PROTEIN RELEASE RATE FROM MYCOPROTEIN - FUSARIUM VENENATUM BY CELL DISRUPTION METHOD - P., Prakash; Namasivayam, S. Karthick Raja (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: Single cell protein based on mycoprotein is now extensively used as human and animal feed in various parts of the world. It is used because of the high nutrient content particularly protein and the supply of protein is an essential criteria of utilization of mycoprotein. The present study is about evaluation of protein release rate from mycoprotein - Fusarium venenatum by cell disruption method. Methods: Fusarium venenatum was cultivated in Vogel's mineral medium and the separated biomass was subjected to lyophilization followed by grinding and sonication under different time periods to release the protein. Liberated protein was estimated by Lowry's method and the protein release rate was determined. Results: Maximum protein release rate constant 0.680 min was recorded in grinding with sonication. Conclusion: Protein release rate from mycoprotein – Fusarium venenatum by cell disruption method is the useful study to determine the optimal utilization of nutrient factors supplied by the mycoprotein to the consumers.Further studies will be helpful to determine the release profile with suitable animal model.